The Co-movement of China And Us Stock Indices: A Portfolio Diversification Analysis - Ahmad Monir Abdullah; Abul Mansur Mohammed Masih; Mariani Abdul Majid; Wai-Yan Wong; Hishamuddin Abdul Wahab (UUM Press, 2024)
Indexed by WOS/Scopus/MYCITE